2022
DOI: 10.1186/s12889-022-14860-9
|View full text |Cite
|
Sign up to set email alerts
|

How effective is the health promotion policy in Sichuan, China: based on the PMC-Index model and field evaluation

Abstract: Background Many countries around the world highlight the health in all policies (HiAP). However, most of the related research focused on the influential factors and implementation strategies, with less concern on the evaluation of HiAP. In response to HiAP's call, the Chinese government has proposed health promotion policies (HPPs) in counties or districts, the evaluation of HPPs in sample counties or districts of Sichuan province in China is an essential basis for optimizing policy content, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…For example, Yang et al ( 49 ) found that the new energy vehicle policy has inadequate incentives for infrastructure construction. Yang et al ( 11 ) conducted a study on 37 health promotion policies that seldom involve incentives. These findings indicate that insufficient incentives are a common problem with policies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Yang et al ( 49 ) found that the new energy vehicle policy has inadequate incentives for infrastructure construction. Yang et al ( 11 ) conducted a study on 37 health promotion policies that seldom involve incentives. These findings indicate that insufficient incentives are a common problem with policies.…”
Section: Discussionmentioning
confidence: 99%
“…We plot the PMC-Surface by calculating the PMC matrix. To meet the balance and symmetry of the matrix, X 10 is left out of this research ( 11 , 46 , 47 ). After removing X 10 , a 3 × 3 matrix is generated by the remaining 9 primary variables, as shown in Eq.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, scholars in China have usually combined another policy analysis method in addition to the PMC index model to carry out quantitative evaluation of the policy, which, from a comprehensive point of view, mainly includes policy tools, semantic network analysis, knowledge mapping, and text analysis [31]. Taken together, this type of research mainly explores the traditional research methods in the field of policy evaluation [32][33][34], the integration of the PMC index model with other research methods [35][36][37].…”
Section: Literature Reviewmentioning
confidence: 99%